Extreme Weather Events and Spiraling Debt: A Double Whammy for Bangladeshis Affected by Climate Change - Atiqul Haq, Shah Md (Frontiers in Psychology, 2022)
The study explores how people living in areas prone to various extreme weather events (e.g. floods, cyclones and droughts) perceive climate change, the impacts they face and how they cope with the consequences of extreme weather events (EWEs) in Bangladesh. The study used convenient sampling to collect data through in-depth interviews with 73 respondents, including men aged 30-34 and women aged 20-24. The results of the study show that there are similarities and differences in respondents' views on the importance of climate change, the causes of climate change, the consequences of EWE and strategies to address EWE. The study did not focus on gender perspectives, but there are differences in views from a gender perspective. People in the three vulnerable areas defined climate change based on their experiences of climate change and EWE and expressed their views based on their experiences of where they live. One of the main findings of the study is that people in the three areas borrow as a survival strategy. They indicated that they needed money immediately to survive and support their families. As the climate will change rapidly and EWEs will occur frequently and regularly, people have to cope with the impact of these events and live with the challenges as a routine. Regular borrowing of money from creditors becomes a "money debt" for vulnerable people. This is exacerbated by the regular impacts of EWE. This can be described as a spiraling trap and a double whammy: on the one hand through climate change and EWE, and on the other through borrowing money in times of crisis.